Implementasi Manajemen Tata Usaha di SMK Negeri 3 Kabupaten Raja Ampat - Rahmadani, Nur Fitri; Sudirman; Keliata, Anda (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2023)
As the educational world develops, the challenges and dynamics faced by modern schools are becoming more complex, requiring special attention to managerial aspects. Schools that are effective in implementing business management can optimize resource use, increase transparency, and provide better educational services to students and parents. The purpose of this study is to find out about the implementation of business management implemented at SMK Negeri 3 Raja Ampat. The research method used in this study is field observation or field research with a qualitative approach. The data sources in this study are divided into 2 primary and secondary data sources. The results of this study show that the implementation of business management in SMK Negeri 3 Raja Ampat Regency has not been fully implemented so the implementation has not been optimal. There are some things that cause this include a lack of coordination between the teaching staff and the principal.